Interest as an agency in mental development - McCampbell, Charles Wilber (My University, 1906)
Introduction: "Interest is the greatest word in education". These words of President Schuman greatly impressed me. They set me to thinking and studying upon this subject and the more I study it the more I am convinced of the truth and wisdom of his statement. It is my purpose to try to show what we mean by the doctrine of interest and the part it plays in Mental development. We may say in general that interest is a feeling that accompanies the idea of self-expression. It has its origin in the exhilaration, the sense of power, of mastery, that goes with every internally impelled effort to realize a condition for the survival of the self, whether such survival touch one aspect of the man or another. Interest is therefore dynamic in character. It has its primary root in inherited impulse. We have impulses to eat, to run, to hunt, to work, to talk, to play, to avoid dangers, to seek pleasure. But these impulses with Modern men, as with primitive people are always directed toward some object, in the approach of which we find the realization of some aspect of our mental or physical being. There is no break between the impulse and the self; for the impulse is nothing more than the involuntary, and perhaps almost conscious, effort at self-expression. What we mean by the doctrine of interest is that the interest naturally attaching to the ends for which pupils study should be awakened in the means used for reaching them; and conversely, that permanent interest in the ends should be fostered through the means. When interest attaches to the end, but not to the means for reaching it, we have drudgery, as in the case of a workman who thinks only of the dollars, taking no pride or interest in the labor that earns it; on the other hand when there is interest in the means but none in the end, we have play not work. Interest is then only amusement. When however, there is interest in the end to be attained by activity, and also by the means for reaching the end, we have the type of work desirable in education.
Citation: McCampbell, Charles Wilber. Interest as an agency in mental development. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Theses